ANALISIS VALIDITAS DAN RELIABILITAS SOAL ALJABAR UNTUK SISWA SEKOLAH MENENGAH PERTAMA: STUDI KUANTITATIF - Moh. Abdul Qohar; Faiz Fauziyah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2024)
This study aims to analyze the validity and reliability of an algebra test instrument designed for middle school students. The background of this research lies in the importance of mathematics education, particularly algebra, which serves as a foundation for other branches of mathematics. Based on the 2021 PISA data, the learning outcomes in mathematics, especially algebra, in Indonesia remain weak. Therefore, valid and reliable evaluation instruments are essential to accurately measure students' competencies. This study employs a quantitative descriptive approach with a purposive sampling of 15 ninth-grade students from MTs Al Amiriyyah. The instrument, consisting of algebra essay tests, was tested for validity using the Pearson Product Moment method and for reliability using the Cronbach's Alpha method. The results indicate that out of 10 test items, 9 items (90%) were declared valid with r_calculated > r_table (0.4409), while 1 item (10%) was invalid. The Cronbach's Alpha value of 0.924, which is greater than 0.60, indicates a very high level of reliability. According to Guilford's category, the instrument demonstrates high credibility as an evaluation tool. These findings suggest that the algebra test instrument is reliable for measuring students' competencies and provides empirical contributions to improving the quality of algebra learning evaluations. Keywords: validity, reliability, test instrument, algebra, learning evaluation.